Comparison of the Efficacy of Latanoprost, Bimatoprost, and Travoprost in Patients with Primary Open-Angle Glaucoma and Ocular Hypertension - Nur Çolak; Aydın Yıldırım; Haşim Uslu; Bülent Gürler (Türk Oftalmoloji Dergisi, 2014)
Objectives: The aim of this prospective study was to compare the efficacy of latanoprost, bimatoprost, and travoprost in lowering intraocular pressure (IOP) and in preventing or delaying visual field loss in patients with primary open-angle glaucoma (POAG) and ocular hypertension (OH). Materials and Methods: The study included 124 eyes of 73 patients who were diagnosed in our clinic as having POAG or OH. All of the patients had IOP values of 22-34 mmHg, an early diagnosis of POAG or OH, without any previous treatment. The patients were randomly divided into 3 Groups: Group 1; 42 eyes treated with latanoprost (0.005%), Group 2; 40 eyes treated with bimatoprost (0.03%), and Group 3; 42 eyes treated with travoprost (0.004%). The visual field has been evaluated via the Humprey visual field evaluation of statistical program Statpac mean deviation (MD) and pattern standard deviation (PSD). The IOP, MD, and PSD values have been measured initially and at the end of the first year of treatment. Results: In comparison to the baseline, the mean changes of IOP values after one year of treatment were 6.99, 6.79 and 5.87 mmHg for the 3 Groups, respectively. The decrease in the IOP was statistically significant for each of the treatment groups (p<0.001), with insignificant differences between the groups (p>0.05). Comparison of the MD and PSD values revealed no significant differences among the treatment groups both initially and at the end of the first year (p>0.05). The mean changes in MD and PSD values at the end of the first year were similar among the treatment groups (p>0.05). Conclusion: In patients with POAG and OH, treatment with latanoprost, bimatoprost, and travoprost decrease the IOP effectively. After a one-year treatment, no significant difference has been found between the efficacy of the 3 drugs in lowering IOP and in preventing or delaying visual field loss. (Turk J Ophthalmol 2014; 44: 170-4)